Intranasal curcumin and its evaluation in murine model of asthma - Subhashini; Chauhan P.S.; Kumari S.; Kumar J.P.; Chawla R.; Dash D.; Singh M.; Singh R. (My University, 2025)
Curcumin, a phytochemical present in turmeric, rhizome of Curcuma longa, has been shown to have a wide variety of pharmacological activities including anti-inflammatory, anti-allergic and anti-asthmatic properties. Curcumin is known for its low systemic bioavailability and rapid metabolization through oral route and has limited its applications. Over the recent decades, the interest in intranasal delivery as a non-invasive route for drugs has increased as target tissue for drug delivery since nasal mucosa offers numerous benefits. In this study, we evaluated intranasal curcumin following its absorption through nasal mucosa by a sensitive and validated high-performance liquid chromatography (HPLC) method for the determination of intranasal curcumin in mouse blood plasma and lung tissue. Intranasal curcumin has been detected in plasma after 15 min to 3 h at pharmacological dose (5 mg/kg, i.n.), which has shown anti-asthmatic potential by inhibiting bronchoconstriction and inflammatory cell recruitment to the lungs. At considerably lower doses has proved better than standard drug disodium cromoglycate (DSCG 50 mg/kg, i.p.) by affecting inflammatory cell infiltration and histamine release in mouse model of asthma. HPLC detection revealed that curcumin absorption in lungs has started after 30 min following intranasal administration and retained till 3 h then declines. Present investigations suggest that intranasal curcumin (5.0 mg/kg, i.n.) has effectively being absorbed and detected in plasma and lungs both and suppressed airway inflammations at lower doses than the earlier doses used for detection (100-200 mg/kg, i.p.) for pharmacological studies (10-20 mg/kg, i.p.) in mouse model of asthma. Present study may prove the possibility of curcumin as complementary medication in the development of nasal drops to prevent airway inflammations and bronchoconstrictions in asthma without any side effect. © 2013 Elsevier B.V.